Transformasi Studi Hadis Tematik: Pengertian, Pertumbuhan, dan Sejarahnya: The Transformation of Thematic Hadith Studies: Definition, Development, and Historical Background - Juhariyah Juhariyah; Repa Hudan Lisalam; Muhammad Alif; Muhammad Afif (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This Thematic hadith studies (mauḍū‘ī) are one of the approaches to understanding hadith by collecting various narrations related to a specific theme and then analyzing them comprehensively, systematically, and in-depth. This method does not only examine the textual aspects of the hadith but also considers its context, meaning, as well as its social and historical relevance. This research aims to explore the definition, development, and historical growth of thematic hadith studies across different periods, in order to understand its existence as a relevant and applicable method of hadith analysis. Using a descriptive qualitative approach based on literature review, the study finds that thematic hadith studies have been implicitly recognized since the early period of Islam, later developed more systematically during the codification era, and gained significant scholarly and academic attention in the modern era. The findings show that this approach offers a more comprehensive, integrative, and contextual understanding of hadith, and provides more appropriate responses to various contemporary Islamic issues in a thematic and relevant manner aligned with the dynamics of the times.